Local government transformation glimpses from the local finance literature under the 1991 local government code - Ilago, Simeon A. (1997)
Although still mainly traditional in terms of local financing, local government units (LGUs) have increasingly taken advantage of the facilitating framework for revenue generation provided by the Local Government Code of 1991. LGUs are trying to improve their tax be abreast with modern developments in the field like computerization of tax administration and networking of offices. They have also ventured into roles which are enabling in nature along with their traditional functions as direct service provider and employer.
Keywords: Local government -- Finance; Internal revenue allotment; Decentralization; Local government laws; Local Government Code